PENGELOLAAN BAITUL MAAL PADABAITUL MAAL WA TAMWIL (BMT) DI KOTA PEKALONGAN - Kuat Ismanto (JURNAL PENELITIAN, 2015)
Baitul Maal wa Tamwil (BMT) is a microfinance institution that operates based on Islamic principles (Islam). There are two main divisions of the institution, as a business base that is as Baitul Maal and as Baitul Tamwil. The first division related to social mission, namely as zakat management institutions, infaq, endowments, charity, and others, while the second division is engaged in the business (profit). This paper further review of Baitul Maal position/status at BMT, then discussed how the management of funds by the agency. Facts on the ground indicate that there is BMT has run Baitul Maal, however many do not run it.